2000
DOI: 10.1016/s0002-9440(10)64510-5
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Endothelial Growth Factor-C and Its Receptor VEGFR-3 in the Nasal Mucosa and in Nasopharyngeal Tumors

Abstract: In the nasal mucosa, unlike in other parts of the respiratory tract, the permeability of the capillaries and small venules is very high, and their endothelium is typically fenestrated.1 The abundant nasal and nasopharyngeal blood and lymphatic vessels and factors regulating the permeability of the capillary endothelia are of great clinical significance in inflammatory and infectious diseases as well as in tumors. Nasopharyngeal squamous cell carcinomas often remain small and asymptomatic, even after widespread… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
25
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 29 publications
7
25
0
Order By: Relevance
“…The vessel specific protein (VEGFR3 or CD34) is then kept upregulated, whereas the respective other protein ceases. This thesis is in line with results published recently in nasal 36 and breast carcinomas, 32 in which VEGFR3 and PAL-E coexpression has been described in tumor vessels in a similar fashion. Double staining of VEGFR3 and VEGFR2 in HNSCC was rare.…”
Section: Vegf-c Expression In Hnsccsupporting
confidence: 92%
“…The vessel specific protein (VEGFR3 or CD34) is then kept upregulated, whereas the respective other protein ceases. This thesis is in line with results published recently in nasal 36 and breast carcinomas, 32 in which VEGFR3 and PAL-E coexpression has been described in tumor vessels in a similar fashion. Double staining of VEGFR3 and VEGFR2 in HNSCC was rare.…”
Section: Vegf-c Expression In Hnsccsupporting
confidence: 92%
“…It is known that nasal mucosa typically contains large numbers of lymphatic vessels which play a crucial role in different complaints such as inflammatory diseases [19]. In our study, we found numerous lymphatics labeled by D2-40 in the periphery and in the center of SHP.…”
Section: Discussionsupporting
confidence: 61%
“…VEGFR-3 expression in tumor cells has been reported in patients with malignant mesothelioma, 35,40 Kaposi sarcoma, 41 vascular tumors, 42 nasopharyngeal tumors, 43 and adenocarcinoma of the lung. 44 These reports evaluated VEGFR-3 expression in vascular endothelial cells but not in tumor cells.…”
Section: Discussionmentioning
confidence: 99%